KEBIJAKAN PEMBANGUNAN â€œSIJORIâ€ DAN DAMPAKNYA TERHADAP KEBUDAYAAN - Sutamat Aribowo (LIPI Press, 2009)
In the New Order era, President Soeharto, Prime Minister Mahathir Muhammad, and Prime Minister of Lee Kuan Yew developed a cooperation among three nearby states, which called â€œgrowth triangleâ€ Singapura - Johor - Riau (Sijori). The approach used at that moment was â€œcomparative advantageâ€. As a consequence of this approach, its orientation tends to be more quantitative rather than qualitative. Caring less for the qualitative issue has made the approach â€˜ignoreâ€™ the problems of culture. Therefore, policies executed following the paradigm of â€œgrowth triangleâ€ Sijori were merely seen from the perspective of economic and politics. This article tries to reflect and converse the cooperation of â€œgrowth triangleâ€ in Kepulauan Riau from the perspective of culture. Particularly in answering the question on how the policies of culture in this area at past, present, and the future are. Keyword: Politics of culture, development policy, Sijori, Malayâ€™s world.